Optimization Strategies, Kinetics and Modeling of Cell Growth in Centella Asiatica Cell Culture - Omar, Rozita (2003)
C. asiatica (Umbelliferae) or locally known as "pegaga" cell suspension culture is used as a model system to produce triterpenoids (TTPs). Cell growth and TTPs production were optimized at shake flask level. Different factors such as nutritional requirement and environmental conditions were screened and optimized using Response Surface Methodology (RSM) experimental design. Preliminary study of laboratory-scale bioreactor was done to study cell growth at regulated pH. Kinetics and modeling studies were carried out aimed at evaluating growth and production parameters for better understanding and control of the process. This study was conducted as foundation for production of triterpenoids at commercial scale. Growth medium (G) was developed for optimum cell growth by manipulation of different inoculum age and size, sucrose concentration, hormone combination and concentration, incubatOptimization strategies by RSM has established cell growth of C. asiatica above 16 g L⁻¹ at 25°C, pH 5.65 and light intensity of 734 lux; medium NH₄⁺:NO₃⁻ ratio between 0.45-0.9, higher pol-at 2.6 mM, sucrose concentration around 6.68% in combination with 0.84 mg L⁻¹ IAA and 1.17 mg L⁻¹ BAP and higher total number of nitrogen around 40 mM. Maximum cell dry weight around 27 g L⁻¹ was attained with G medium. However, TTPs production was not significantly affected by all factors because of very low production. Cell growth rate at 0.09 day⁻¹ (td=7.5 days) was 1.5 times higher when medium pH was controlled at pH 4 in stirred-tank: bioreactor. However, maximum cell dry weight at 8.6 g L⁻¹ was 1.5 times higher when pH was not controlled, with in almost three times more efficient sucrose utilization at 0.28 g cell g⁻¹ sucrose. Higher growth rate at 0.18 day⁻¹ in bioreactor cultivation (B) was only 20% higher than shake flask cultivation However, maximum cell dry weight at 10.5 g L⁻¹ in M was 14% higher than in B.A 97% confidence was achieved by fitting three unstructured growth models; Monod, Logistic and Gompertz equations to the cell growth data. The deviation in Logistic and Gompertz models could be due the model was developed for substrateindependent growth and fungi growth, respectively.